Численная эффективность методов полуопределенной оптимизации - Косолап, А.И.; Перетятько, А.С. (Проблемы управления и информатики, 2014)
Розглянуто задачі напіввизначеної оптимізації та методи їх розв’язання. Запропоновано новий узагальнений симлекс-метод для розв’язання задач напіввизначеної оптимізації на основі апроксимації конуса напіввизначених матриць сумою матриць рангу одиниця. Порівняльні чисельні експерименти підтверджують ефективність напіввизначеного симплекс-методу. The problems of semidefinite optimization and modern methods of their solution are considered. The new semidefinite simplex-method for the solution of problems of semidefinite optimization on the basis of approximation of a cone of semidefinite matrixes by the sum of matrixes of a rank unit is offered. Comparative numerical experiments have confirmed the efficiency of the semidefinite simplex-method.